And Thou Shalt Honor: children's caregiving, work and religion - Fernanda Mazzotta; Francesca Bettio; Valentina Zigante (Global Labor Organization (GLO), 2018)
In this paper we take a fresh look at the magnitude of the trade-off between caring informally for a parent and paid work. We adopt a simultaneous approach with a primary focus on how hours of care are influenced by hours of work rather than the other way round. We also investigate the role that filial obligations play in choices of caring versus working. Using the SHARE data (2004 and 2006) we find that the elasticity of informal care hours in response to working hours is around -0.18, small but not negligible. Moreover, we find that a one point decrease out of a seven point index measuring the strength of filial obligations reduces weekly hours of care by about one hour and half.
Keywords: I11; I12; J22; D10; Z10; 330; Informal care; caregiver; culture; endogeneity; Europe; SHARE